Integration of Science and Religion in Indonesian and Malaysian Students Perception: Is it Different? - Siti Khoiriyah; M Faishal Khoirurrijal; Hasan Ruzakki; Karim, Abdul Rahim (Program Pascasarjana Universitas Ibrahimy, 2025)
The intricate relationship between science and religion has long been a provocative subject of discussion among scholars in higher education. In recent years, the pursuit of integrating these two seemingly disparate fields has emerged as a pivotal approach for universities aiming to evolve into more holistic institutions across diverse scientific disciplines. UIN Maulana Malik Ibrahim Malang in Indonesia and the International Islamic University Malaysia (IIUM) are prominent examples of this integration paradigm. This research aims to explore how UIN Maulana Malik Ibrahim Malang and IIUM students perceive the interplay between science and religion, particularly in the context of their classroom experiences. Employing a quantitative methodology, this study utilizes a comparative descriptive approach alongside a case study strategy to gather insights. Findings from the research reveal a remarkable consensus among students from both universities. They overwhelmingly agree that a dialogical and integrative typology characterizes the relationship between science and religion. This shared perception underscores a mutual understanding of the relevance and interconnectedness between these two fields. Furthermore, students strongly affirm the effective incorporation of this integration within their classroom learning environments. Such a consensus not only recognizes the relationship but also suggests a positive influence on their educational experiences, reinforcing the idea that the synergy between science and religion can profoundly enrich academic pursuits.